2015
DOI: 10.1037/a0039650
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feedback on energy conservation: A meta-analysis.

Abstract: Feedback has been studied as a strategy for promoting energy conservation for more than 30 years, with studies reporting widely varying results. Literature reviews have suggested that the effectiveness of feedback depends on both how and to whom it is provided; yet variations in both the type of feedback provided and the study methodology have made it difficult for conclusions to be drawn. The current article analyzes past theoretical and empirical research on both feedback and proenvironmental behavior to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
202
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(240 citation statements)
references
References 109 publications
6
202
1
7
Order By: Relevance
“…This finding adds to an existing body of research where feedback employing social comparison failed to promote conservation efforts (e.g., [10]; see also [6]). One reason for why norm-based interventions may be ineffective is a lack of credibility of the conveyed information [45].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This finding adds to an existing body of research where feedback employing social comparison failed to promote conservation efforts (e.g., [10]; see also [6]). One reason for why norm-based interventions may be ineffective is a lack of credibility of the conveyed information [45].…”
Section: Discussionmentioning
confidence: 67%
“…Feedback can instigate behavioural change because recipients are made aware of the consequences (positive or negative) associated with the targeted behaviour [5]. Whilst many studies attest to the effectiveness of feedback in promoting conservation behaviour, there is also evidence that effects vary as a function of how and to whom feedback is presented [6]. This paper focuses on social comparison feedback, which is when people receive feedback about their own ecological footprint relative to the ecological footprint of the average member of a reference group (cf.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted here that people, in general, tend to stop engaging with feedback after some time, which necessitates the development of innovative methods (to supplement energy audits) to communicate with the energy users in households [17,19,20]. A review on earlier research on energy advising shows that research indicates that a measurement-feedback-communication strategy for households is necessary if one wishes to effect a change in consumer behavior [20,21].…”
Section: Energy Policy Targeting Households: a Backgroundmentioning
confidence: 99%
“…Johnson et al 2002) as choice-architectdesigned reference points have been shown to be effective in motivating consumers to make choices that improve both their and social welfare (Beshears et al 2007), particularly where consumers perceive the 'effort tax' (Sunstein 2013) to override the default as too high. At the same time, however, defaults have to be credible and salient (Sunstein 2013); otherwise, they fail to provide a suitably accurate or relevant feedback mechanism to affect consumer choice change (Karlin et al 2015). Energy savings from a more efficient specific appliance purchase, shown to the consumer in a dollar amount and predicated on salient default values (e.g.…”
Section: Introductionmentioning
confidence: 99%